The development of methods for the determination of residues of the herbicide halauxifen-methyl in barley and rape - Zayats, Mikhail F.; Leschev, Sergey M. (Journal of the Belarusian State University. Chemistry, 2019)
Optimal conditions for the extraction of halauxifen-methyl from grain, straw and green mass of barley; seeds, oil and green mass of rape, as well as the conditions for the purification of extracts were selected on the basis of the distribution constants (P) and distribution coefficients (D) experimentally determined at a temperature of (20 ± 1) °C. At the first stage, acetonitrile, or acidified acetonitrile, or a mixture of water and acetonitrile were used to extract the pesticide. Halauxi fen-methyl was found to be a weakly hydrophobic substance and it exhibits the properties of a weak base in aqueous solutions. For the purification of plant material extracts hexane – 1 mol/L aqueous solution of hydrochloric acid and hexane – 10 % K2HPO4 aqueous solution were successfully used (to neutralize the acid and increase the extraction constant due to the salting out effect). The samples obtained after purification are sufficiently pure. So, the residual amounts of halauxifen-methyl can be determined by widespread liquid chromatography with diode array (ultraviolet) detection at the level, which is equal or lower to the maximum allowable content of herbicide in barley and rape.